2022
DOI: 10.4018/978-1-6684-5523-4.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Brand Attachment and Agile Marketing

Abstract: This research seeks to understand the impact of the pandemic on online sales of sports brands and their relationship with consumers. The results obtained showed that the brands adapted to the pandemic period, they managed to preserve and even strengthen the relationship and communication with their consumers due to their online platforms, in which their sports products were found due to the high demand during the pandemic, especially in the period of confinement. In addition to realizing the importance of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Several researchers have concluded that brand love is positively influenced by brand attachment (Hadi and Ahmed 2018;Ghorbanzadeh and Rahehagh 2020;Gumparthi and Patr 2020;Japutra et al 2018;Vieira and Sousa 2020). This is due to the fact that brand attachment is seen by many authors as an antecedent of brand love (Gumparthi and Patr 2020;Japutra et al 2018;Roy et al 2016;Cardoso and Sousa 2020;Reis et al 2023). The relationship of attachment and love for the brand can be compared to an interpersonal relationship.…”
Section: Brand Attachment and Brand Lovementioning
confidence: 99%
“…Several researchers have concluded that brand love is positively influenced by brand attachment (Hadi and Ahmed 2018;Ghorbanzadeh and Rahehagh 2020;Gumparthi and Patr 2020;Japutra et al 2018;Vieira and Sousa 2020). This is due to the fact that brand attachment is seen by many authors as an antecedent of brand love (Gumparthi and Patr 2020;Japutra et al 2018;Roy et al 2016;Cardoso and Sousa 2020;Reis et al 2023). The relationship of attachment and love for the brand can be compared to an interpersonal relationship.…”
Section: Brand Attachment and Brand Lovementioning
confidence: 99%
“…Com isto o mercado se viu obrigado a se adaptar a atual situação de acordo com o novo estilo de vida imposto a seus consumidores. Para suprir a necessidade de compras, a internet foi o meio mais usado para todos os tipos de consumo e consumidores (Reis et al, 2023).…”
Section: Introductionunclassified